The Relationship Between Obesity and Type 2 Diabetic in Productive Age at Puskesmas Karya Wanita - Ami Amelia; Arnila Melina; Sukmawati Sukmawati (Pusat riset dan Inovasi Nasional, 2025)
Background: In 2021, there were 19.5 million diagnosed cases of Type 2 Diabetes Mellitus (T2DM) in Indonesia. In Riau Province, T2DM ranked fifth among the most common conditions treated at community health centers in 2022. Obesity, a major risk factor for T2DM, had a national adult prevalence of 21.8% (Riskesdas 2018) and 24.1% in Riau. At Puskesmas Karya Wanita, 483 new T2DM cases were recorded in 2024, with 434 patients having a BMI ≥ 25 kg/m². The productive age group is particularly at risk for obesity and T2DM, yet screening remains suboptimal. Therefore, research on the relationship between obesity and T2DM at this primary healthcare facility is essential.Objective: To determine the association between obesity and the incidence of T2DM among individuals of productive age at Puskesmas Rawat Inap Karya Wanita, Pekanbaru.Methods: This was a quantitative analytic observational study with a cross-sectional design. The sample included productive age outpatients at the general clinic of Puskesmas Karya Wanita, selected using quota sampling. Data were analyzed using univariate, bivariate (Chi-square test), and Odds Ratio analyses.Results: A significant association was found between obesity and T2DM (p = 0.0029), with an Odds Ratio of 4.517.Conclusion: There is a significant relationship between obesity and T2DM in the productive age group. Individuals with obesity are 4.517 times more likely to develop T2DM compared to those without obesity.